Pengembangan Lembar Kerja Peserta Didik Berbasis Realistics Mathematics Education Materi Bangun Datar Siswa Kelas III Sekolah Dasar - Radial Pansyah Ramadoni; Liza Murniviyanti; Ali Fakhrudin (Journal on Education, 2023)
Based on observations made by researchers at SD Negeri 16 Banyuasin I that researchers found several problems encountered especially in mathematics subjects such as not optimal math scores and not optimal data structure material, this was due to lack of study time and not yet using a learning model that in accordance. With these problems, the research developed a student worksheet based on realistic mathematics education material for class III student data. This study aims to develop student worksheets that are valid and practical. This study uses a level 1 R&D research and development model which consists of several stages of Analysis (potentials and problems as well as data collection), Design, Development (product validation), Implementation and Evaluation. the N-Gain result of 0.84 based on the classification or classification of the N-Gainp interpretation in table 3.9 chapter III student learning outcomes have increased and student worksheets based on realistic mathematics educational materials building data are recorded as effective for use in the teaching and learning process in elementary schools . The results of this study obtained the percentage of experts by 76.66%, the percentage of teacher response questionnaires was 92%, the percentage of student response questionnaires was 82%. The results of this study indicate that the worksheets of students based on mathematics education material for building data for class III elementary school students are feasible to use.